Prevalence and determinants of cervical cancer screening among women aged 15–49 years in Tanzania: analysis of demographic and health survey 2022 - Gladys Reuben Mahiti; Jovinary Adam; Pankras Luoga (Archives of Public Health)
Abstract Background In Tanzania, cervical cancer is the fourth leading cause of cancer-related deaths and the foremost type of cancer affecting women of reproductive age (15–49 years) and beyond. Cervical cancer is preventable and treatable, which underscores the importance of early screening. This study aimed to determine the prevalence and determinants of cervical cancer screening(CCS) among women of reproductive age (15–49) in Tanzania. Methods In this study we analysed secondary data of 15,254 women drawn from the 2022 Tanzanian Demographic and Health Survey (TDHS). Data were weighted using the individual weight for women (v005/1,000,000) according to DHS guidelines. The dependent variable was CCS status, while independent variables included demographic characteristics, socio-economic factors, and health system factors. Descriptive analysis was used to show the distribution of respondents in terms of frequency and percentage. Weighted binary logistic regression model was used to determine associations between the variables. In addition, multivariable logistic model was used to control confounders and assess possibility of interaction. A significance threshold of p-value < 0.05 at 95% confidence interval(CI) was applied to assess the significance of each variable. Results The prevalence of women aged 15–49 years who have ever undergone CCS in Tanzania was 7% (95% CI: 6.58, 7.93). Despite the low proportion of women who have ever received screening, cervical screening was significantly more common among women aged 30–49 years (adjusted Odds Ratio (aOR) = 3.56, 95% CI = 2.75, 4.60), married (aOR = 1.44, 95% CI = 1.11, 1.87), separated individuals (aOR = 1.64, 95% CI = 1.20, 2.24), smokers (aOR = 11.75, 95% CI = 1.93, 71.60), living with HIV (aOR = 5.72, 95% CI = 4.33, 7.56), and those who listened to the radio at least once a week (aOR = 1.46, 95% CI = 1.20, 1.78). Conversely, women who were less likely to be screened for CCS were typically characterised by residing in rural areas (aOR = 0.66, 95% CI = 0.53, 0.82), having informal education (aOR = 0.43, 95% CI = 0.30, 0.60), from low economic backgrounds (aOR = 0.49, 95% CI = 0.37, 0.66), unemployed (aOR = 0.78, 95% CI = 0.65, 0.952), never using contraception (aOR = 0.82, 95% CI = 0.70, 0.97), never covered by health insurance (aOR = 0.58, 95% CI = 0.45, 0.74). These factors were significantly associated with the uptake of CCS services among women aged 15–49 years in Tanzania. Conclusion The study highlight that women aged 15–49 years who have ever undergone CCS in Tanzania is generally low at 7%, compared to the WHO recommendation of 70%. Women with no formal education or primary education, belonging to the poor wealth quintile, and having no access of listening to the radio at least once per week; had lower possibility of undergoing CCS compared to their counterparts. Tailored programs aimed at increasing cervical cancer screening should target all women in order to attain the WHO recommendation. Additionally, there is a need to enhance education and health insurance coverage among community members to increase women’s accessibility to CCS services.